The size, morphology, site, and access score predicts critical outcomes of endoscopic mucosal resection in the colon - Sidhu, Mayenaaz; Tate, David J.; Desomer, Lobke; Brown, Gregor; Hourigan, Luke F.; Lee, Eric Y. T.; Moss, Alan; Raftopoulos, Spiro; Singh, Rajvinder; Williams, Stephen J.; Zanati, Simon; Burgess, Nicholas; Bourke, Michael J. (Endoscopy, 2018)
Background The SMSA (size, morphology, site, access) polyp scoring system is a method of stratifying the difficulty of polypectomy through assessment of four domains. The aim of this study was to evaluate the ability of SMSA to predict critical outcomes of endoscopic mucosal resection (EMR).Methods We retrospectively applied SMSA to a prospectively collected multicenter database of large colonic laterally spreading lesions (LSLs) ≥ 20 mm referred for EMR. Standard inject-and-resect EMR procedures were performed. The primary end points were correlation of SMSA level with technical success, adverse events, and endoscopic recurrence.Results 2675 lesions in 2675 patients (52.6 % male) underwent EMR. Failed single-session EMR occurred in 124 LSLs (4.6 %) and was predicted by the SMSA score (P < 0.001). Intraprocedural and clinically significant postendoscopic bleeding was significantly less common for SMSA 2 LSLs (odds ratio [OR] 0.36, P < 0.001 and OR 0.23, P < 0.01) and SMSA 3 LSLs (OR 0.41, P  < 0.001 and OR 0.60, P = 0.05) compared with SMSA 4 lesions. Similarly, endoscopic recurrence at first surveillance was less likely among SMSA 2 (OR 0.19, P < 0.001) and SMSA 3 (OR 0.33, P < 0.001) lesions compared with SMSA 4 lesions. This also extended to second surveillance among SMSA 4 LSLs.Conclusion SMSA is a simple, readily applicable, clinical score that identifies a subgroup of patients who are at increased risk of failed EMR, adverse events, and adenoma recurrence at surveillance colonoscopy. This information may be useful for improving informed consent, planning endoscopy lists, and developing quality control measures for practitioners of EMR, with potential implications for EMR benchmarking and training.